Collaborative Governance In The Development Of Tourist Village In Karangsalam Village, Baturaden District, Banyumas Regency - Chamid Sutikno; Zaula Rizqi Atika; Shadu Satwika Wijaya; Andi Zaelani (DYNAMICS: Journal of Public Administration, 2022)
Tourism is one of the important sectors that has great opportunities in the community to be developed. The development of tourism in Indonesia is expected to be able to make a major contribution to the economy in Indonesia. In addition, the existence of tourism in Indonesia can also improve the welfare of the community, where Indonesian tourism is a development of the tourism village-based tourism model. One of the tourism village-based tourism is in Banyumas Regency, namely Karangsalam Tourism Village. This village forms a tourist village with the aim of making the people in it independent. The research method used is descriptive research with a qualitative approach. The focus of the research is the aspect of the collaborative governance model which is focused on the Tourism Village in Karangsalam Village, Baturaden District, Banyumas Regency. The informants of this research were the Head of Karangsalam Village, Director of Tourism Village and Management, Village Supervisory Board, and the environmental community around Karangsalam Village. Data collection techniques are interviews, observation and documentation. The data analysis technique uses the Cresswell analysis model, while the data validity uses triangulation to obtain valid data. The results of this study indicate the form of the collaborative governance process carried out, namely to analyze the development of tourist villages in Karangsalam Village, Baturaden District, with the Tourism Village in Karangsalam Village being able to make the community independent from various community affairs and increase local community income and specifically be able to contribute to the village's original income.